Liposarcoma of the Tongue - M. Šafářová; O. Moztarzadeh (Czech Dental Chamber, 2008)
The authors of this case report are describing a rare tumor (well-differentiated liposarcoma ═ WDLS) in the orofacial region of a 93-year-old man. At the same time they are presenting a brief review about malignant adipose tissue tumors.